Quantitative Phytochemical Analysis and Acute Toxicity Study of Ficus racemosa - A.Naga Teja Pavani; D. Sheela; Sailaxmi Venepally (The Bioscan, 2024)
Background Ficus racemosa is a medicinal plant traditionally used for its therapeutic benefits. This study aims to quantify key phytochemicals and evaluate the acute toxicity of Ficus racemosa to establish its safety profile. Methods A quantitative analysis of Ficus racemosa extract was conducted to measure the concentrations of flavonoids, phenols, and alkaloids. Wistar rats were utilized in acute toxicity research. They received a single oral dosage of 2000 milligrams per kilogram of body weight of Ficus racemosa extract for a duration of fourteen days, the animals were monitored for indications of toxicity, such as alterations in their behavior, body mass, or deaths. Gross histopathological examinations of vital organs (liver, kidney, and heart) were performed to assess potential toxic effects. Results The quantitative analysis indicated significant concentrations of flavonoids and phenols, suggesting antioxidant and anti-inflammatory potential. The acute toxicity study showed no toxicity indicators,without any alterations in behavior, body weight, or at dosages as high as 2,000 mg per kilogram body weight.Gross histopathological examination revealed no significant tissue damage in the vital organs like liver, kidney, or heart. Conclusion Ficus racemosa is rich in phytochemicals especially flavonoids and phenols and has no lethal dose up to 2000mg/kg of the body weight. These results justify the traditional usage of Ficus racemosa and provide a basis for its secure therapeutic use. More pharmacological investigations are suggested in order to investigate its potential.